THE STATE OF THE BLOOD AND IMMUNITY SYSTEM IN ATHLETES DURING THE PROCESS OF ADAPTATION TO PHYSICAL ACTIVITIES (Web of Scientists and Scholars: Journal of Multidisciplinary Research, 2025)
Intense physical activity during sports training can negatively impact an athlete's immune system, contributing to the development of secondary immunodeficiency states. These states are characterized by a decrease in the number of immunocompetent cells in the peripheral blood, suppression of the functional activity of T-lymphocytes, decreased levels of interleukins and interferons, disruption of cooperative cellular interactions, and the emergence of autoaggressive clones of B-lymphocytes, leading to autoimmunization. Imbalances in the athlete's immune system can be a pathogenetic mechanism for the development of infectious, tumor, autoimmune, and allergic diseases. Therefore, immune dysfunction is considered a critical factor limiting an athlete's performance. It is known that the intensity and focus of sports training cause biochemical changes not only in muscles and internal organs but also have a significant impact on blood composition and the volume of circulating blood volume. The bone marrow responds to changes in the body's needs under environmental conditions, thereby ensuring the body's adaptation to hypoxia, infection, and blood loss. In response to specific stimuli for each hematopoietic cell line, the proliferative and functional activity of the corresponding colony-forming cells (CFCs) increases. In adulthood, the compensatory responses of all hematopoietic cell lines and the secretion of regulatory hematopoietic cytokines are most appropriate to the current stimulus: hypoxia, infection, and blood loss. Strong stimuli nonspecific to hematopoietic tissue also trigger a response in the blood system, enhancing the body's resistance to environmental factors.